NOVEL BIOMARKERS: THE RENIN-ALDOSTERONE AND ENKEPHALINERGIC SYSTEMS IN DIAGNOSTIC OF KIDNEY CANCER, KIDNEY STONE AND NEPHROPATHY OF RHEUMATOID ARTHRITIS GENESIS - Komarevtsev, V.N.; Balabanova, K.V.; Komarevtseva, I.O.; Karasev, I.E.; Hliebova, T.M.; Shipilova, I.V.; Zhurba, M.A. (World of Medicine and Biology, 2023)
The renin-angiotensin system and endogenous opioids are important bioactive neuropeptides, which are widely distributed in the brain and peripheral regions to produce diverse biological and neurobiological activities. Research evidence demonstrates significant positive as well as negative interactions between the renin-angiotensin system and endogenous opioids. The purpose of the study was to investigate the association between the renin-aldosterone and enkephalinergic systems in patients with kidney cancer, kidney stone and nephropathy of rheumatoid arthritis genesis. Survival and decline in eGFR ≤ 40 % analysis was performed using the Kaplan–Meier method; univariate and multivariate analyses were undertaken using log rank test and Cox’s regression model, respectively. Met-enkephalin has a high prognostic efficacy for assessing the development of end-stage kidney disease in patients with nephrolithiasis. Level activity renin plasma was an independent predictor of decline in glomerular filtration rate in patients with ureteral stones, patients with nephropathy on the background of rheumatoid arthritis and cancer-specific mortality in .patients with renal cell cancer.